Metabolic profiling in serum, cerebrospinal fluid, and brain of patients with cerebrotendinous xanthomatosis - Höflinger, Philip; Hauser, Stefan; Yutuc, Eylan; Hengel, Holger; Griffiths, Lauren; Radelfahr, Florentine; Howell, Owain W.; Wang, Yuqin; Connor, Sonja L.; Duell, P. Barton; DeBarber, Andrea E.; Martus, Peter; et al. (Journal of lipid research, 2021)
Cerebrotendinous xanthomatosis (CTX) is caused by autosomal recessive loss-of-function mutations in CYP27A1, a gene encoding cytochrome p450 oxidase essential for bile acid synthesis, resulting in altered bile acid and lipid metabolism. Here, we aimed to identify metabolic aberrations that drive ongoing neurodegeneration in some patients with CTX despite chenodeoxycholic acid (CDCA) supplementation, the standard treatment in CTX. Using chromatographic separation techniques coupled to mass spectrometry, we analyzed 26 sterol metabolites in serum and cerebrospinal fluid (CSF) of patients with CTX and in one CTX brain. Comparing samples of drug naive patients to patients treated with CDCA and healthy controls, we identified 7α,12α-dihydroxycholest-4-en-3-one as the most prominently elevated metabolite in serum and CSF of drug naive patients. CDCA treatment substantially reduced or even normalized levels of all metabolites increased in untreated patients with CTX. Independent of CDCA treatment, metabolites of the 27-hydroxylation pathway were nearly absent in all patients with CTX. 27-hydroxylated metabolites accounted for ∼45% of total free sterol content in CSF of healthy controls but <2% in patients with CTX. Metabolic changes in brain tissue corresponded well with findings in CSF. Interestingly, 7α,12α-dihydroxycholest-4-en-3-one and 5α-cholestanol did not exert toxicity in neuronal cell culture. In conclusion, we propose that increased 7α,12α-dihydroxycholest-4-en-3-one and lack of 27-hydroxycholesterol may be highly sensitive metabolic biomarkers of CTX. As CDCA cannot reliably prevent disease progression despite reduction of most accumulated metabolites, supplementation of 27-hydroxylated bile acid intermediates or replacement of CYP27A1 might be required to counter neurodegeneration in patients with progressive disease despite CDCA treatment.